Clozapine in Treatment-Resistant Schizophrenia and Its Augmentation with Electroconvulsive Therapy in Ultra-Treatment-Resistant Schizophrenia - Vjekoslav Peitl; Antonia Puljić; Mislav Škrobo; Sergej Nadalin; Lidija Fumić Dunkić; Dalibor Karlović (Biomedicines, 2023)
Clozapine is considered the gold standard for patients with treatment-resistant schizophrenia (TRS) who have previously tried other antipsychotics at adequate doses (two or more, with at least one being atypical). However, despite optimal treatment, a subgroup of TRS patients with what is known as ultra-treatment-resistant schizophrenia (UTRS) fails to respond to clozapine, which occurs in 40–70% of cases. The most common approach to manage UTRS involves augmenting clozapine with pharmacological or non-pharmacological interventions, with a growing body of evidence that supports the use of electroconvulsive therapy (ECT) as an augmenter. This prospective non-randomized 8-week study, which followed the TRIPP Working Group guidelines and is one of few that separate TRS from UTRS, aimed to evaluate the effectiveness of clozapine in TRS patients and the efficacy of ECT augmentation of clozapine in UTRS patients. Patients with TRS were assigned to receive clozapine alone (clozapine group), whereas UTRS patients received bilateral ECT in addition to their current medication regimen (ECT plus clozapine group). The severity of symptoms was evaluated using the Clinical Global Impression Scale (CGI) and Positive and Negative Syndrome Scale (PANSS) at baseline and at the end of the 8-week trial. Both treatment approaches resulted in improved CGI and PANSS scores. The results suggest that both clozapine and ECT are effective treatment options for patients with TRS and UTRS, respectively, and that adherence to guidelines should provide a better frame for future clinical studies.